2016
DOI: 10.1017/jfm.2016.785
|View full text |Cite
|
Sign up to set email alerts
|

Aeroacoustic source mechanisms of a wavy leading edge undergoing vortical disturbances

Abstract: High-accuracy numerical simulations are performed to study aeroacoustic source mechanisms of wavy leading edges (WLE) on a thin aerofoil undergoing vortical disturbances. This canonical study is based on a prescribed spanwise vortex travelling downstream and creating secondary vortices as it passes through the aerofoil's leading edge. The primary aim of the study is to precisely understand the relationships between the vortexinduced velocity perturbation and the wall pressure fluctuation on the WLE geometry. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…Previous work on single-wavelength profiles indicate that the dominant sources are located at the root region Kim et al (2016);Chaitanya et al (2017);Gea-Aguilera et al (2017). The reason for this behaviour has been investigated by Turner and Kim (2017). They showed that the root of the serrated leading edge is the dominant noise source due to the presence of a secondary horseshoe-like vortex system generated by the serrated leading edge, which alters the upstream velocity field, thereby enhancing the source strength at the serration root.…”
Section: A Simple Analytical Model To Predict Noise Reductionsmentioning
confidence: 98%
“…Previous work on single-wavelength profiles indicate that the dominant sources are located at the root region Kim et al (2016);Chaitanya et al (2017);Gea-Aguilera et al (2017). The reason for this behaviour has been investigated by Turner and Kim (2017). They showed that the root of the serrated leading edge is the dominant noise source due to the presence of a secondary horseshoe-like vortex system generated by the serrated leading edge, which alters the upstream velocity field, thereby enhancing the source strength at the serration root.…”
Section: A Simple Analytical Model To Predict Noise Reductionsmentioning
confidence: 98%
“…However, most of these papers were focused on single-wavelength serrated leading edge profiles. The noise reduction mechanism of these profiles has been investigated in detail by [6,[10][11][12][18][19][20][21] and essentially involves a reduction in the source strength everywhere along the serrated leading edge except at the root location. At this location, it has been shown that the source strength per unit edge length is identical to that of a straight edge in [11].…”
Section: A Single-wavelengthmentioning
confidence: 99%
“…The solution is found in Section 3 using separation of variables and the Wiener-Hopf technique. Section 4 contains results for the scattered acoustic far field which we compare to numerical simulations adapted from Turner & Kim (2017). A brief discussion of the adapted numerical method used is given in Section 4.5.…”
Section: Introductionmentioning
confidence: 99%